Postoperative Pain Management after Impacted Third Molar Surgery with Preoperative Oral Lamotrigine, a Randomized, Double-blind, Placebo-Controlled Trial - Hamed Modanloo; Hamidreza Eftekharian; Hamidreza Arabiun (Shiraz University of Medical Sciences, 2018)
Statement of the Problem: Extraction of the impacted third molar is often associated with severe postoperative pains, management of which are a big challenge. Lamotrigine is a new antiepileptic drug with pre-emptive analgesic properties, which is hypothesized to alleviate postoperative pain. Purpose: This study aimed to evaluate the efficacy of pre-operative administration of single oral 200 mg lamotrigine in reducing the postoperative pain of impacted third molar surgery. Materials and Method: In this randomized controlled trial, 100 adult patients were divided into two groups (n= 50) to receive either 200 mg oral lamotrigine or placebo 1 hour before the removal of impacted third molar. The patients were monitored for 4 hours in the recovery room and pain intensity was measured through visual analogue scale (VAS) for the next 12 hours at 30-minute intervals. The time and number of rescue analgesics used in 12 hours was also recorded. Results: Two groups were not statistically significantly different regarding the severity of postoperative pain. (p= 0.512) Conclusion: Accordingly, pre-emptive administration of lamotrigine was not effective in diminishing the postoperative acute pain of impacted third molar extraction.